Performance and robustness characterisation of SiC power MOSFETs - Fayyaz, Asad (2018)
Over the last few years, significant advancements in the SiC power MOSFET fabrication technology has led to their wide commercial availability from various manufacturers. As a result, they have now transitioned from being a research activity to becoming an industrial reality. SiC power MOSFET technology offers great benefits in the electrical energy conversion domain which have been widely discussed and partially demonstrated. Superior material properties of SiC and the consequent advantages are both later discussed here. For any new device technology to be widely implemented in power electronics applications, it’s crucial to thoroughly investigate and then validate for robustness, reliability and electrical parameter stability requirements set by the industry.